Upaya Peningkatan Perkembangan Sosial Emosional Anak Usia Dini Melalui Bermain Peran - Virgin Mulle; Ketty Kase; Falen Lay; Alia Kono; Iren Hede; Fasni Sanam; Norfita Tanau; Fredericksen Victoranto Amseke (FKIP UNSULTRA, 2026)
Child development through role playing and social emotions are important aspects that influence social emotions in early childhood. The aim of this research is to determine the influence of child development through role playing on the social emotional development of children aged 5-6 years. The method in this research is quantitative. The sampling technique was purposive sampling, namely children aged 5-6 years. The respondents for this research were 15 children aged 5-6 years at PAUD Bukit Kasih Baumta Barat. The data collection technique uses a questionnaire with an instrument in the form of a child development scale through role playing and social emotional development. A scale for child development through role playing was developed by Suyadi and Dahlia (2021) called the Inventory of Parent. The social emotional development scale developed by Thompson (2022) is called the social emotional development scale. The data analysis technique is simple linear regression. The results of these findings found that children's development through role playing has a positive and significant effect on the social emotional development of children aged 5-6 years by 83.7%, which means that the more children develop through playing, the more social emotional development of early childhood can be improved. It is hoped that mothers will establish a safe and comfortable relationship with their children, understand the needs and characteristics of children which can influence mental health in the social emotional development of early childhood.